Portfolio managers' and novices' forecasts of risk and return: are there predictable forecast errors? - Muradoglu, Gulnur (Journal of forecasting, 2002)
This study aims to investigate the individual behaviour that underlies the overreaction hypothesis by conducting a controlled experiment. Two areas that were not captured by previous research on the validity of the overreaction hypothesis are investigated. First, actual portfolio managers are employed as forecasters. Second a real‐world assessment task is given in the form of predicting the prices of stocks traded on the exchange on a real time basis. The purpose is to explore return expectations and risk perceptions of portfolio managers as well as financially unsophisticated investors by using point and interval forecasts provided for different forecast horizons in bull and bear markets. Contributions stem from three sources. (1) The use of financially sophisticated subjects for the first time in an experimental framework testing the overreaction hypothesis makes possible to control for the effect of expertise. (2) The use of different forecast horizons controls for the effect of forecast period. (3) The use of real‐time forecasts of specific stocks traded at the stock exchange, for the first time in an experimental framework testing the overreaction hypothesis enables to control for ecological validity. Discussions will be given as to the portfolio managers' versus naive investors' interpolating asset prices from past trends and hedging behaviour, due to their caution in projections of ranges for future prices. Copyright © 2002 John Wiley & Sons, Ltd.